A fundamental study on qualitatively viable sustainable welding process maps. (January 2018) - Sharma, Abhay
Highlights: A new approach for finding process maps in sustainability framework. Quality is 'necessary' but sustainability is 'necessary and sufficient' for manufacturing. Optimal solutions derived from actual specifications are classified as per their sustainability. Diligent use by soft computation should precede physical changes to improve sustainability. Abstract: Welding is a ubiquitous process within manufacturing that also results in some negative environmental impacts due to emissions and inefficient utilization of energy and materials. The conventional approach of obtaining shop-floor applicable welding conditions considering maximum penetration, minimum weld width, minimum dilution, etc. are difficult to simultaneously achieve or if accidently achieved are not necessarily be sustainable and practically applicable. The article proposes an approach for developing welding process maps in sustainability framework. A two-stage approach is presented wherein a number of near-optimal solutions based on realistic quality aspects are acquired through meta-heuristic optimization and Fuzzy classifier is used to assess multiple solutions on the basis of their sustainability. The approach is demonstrated for an actual thick weld considering weld specifications as objectives of optimization and electrical power and material utilization as sustainability aspects in classification. The results show that qualitatively viable sustainable process maps for complex engineering systems can be obtained as a first measure before changes in machine, material or processes are considered. A diligent use of modelling, optimization, and classification in sequence have potential to address the quality and sustainability conflict for a wide variety of products obtained from a process.